PENGEMBANGAN KURIKULUM BAHASA ARAB PADA KELAS MATA PELAJARAN DI MTsN SUMBER BUNGUR PAMEKASAN - Muhlis, Achmad (OKARA: Jurnal Bahasa dan Sastra, 2015)
One of the Among the breakthroughs of MTs Sumber Bungur Pamekasan as a formal educational institution that is trusted as a pilot school in the area of East Java religious ministry is the realization of the program in the field of Arabic language curriculum development. The purpose of this study was about to describe how the concept and development of the classroom curriculum model inÂ Arabic subject atÂ MTsÂ Sumber Bungur Pamekasan, and what are the factors supporting and hindering the implementation of the curriculum. The research result shows thatÂ the class curriculum of Arabic subjects is basically develop the 2006 curriculum which emphasis on the needs of the community and the islamic boarding school. MTsÂ Sumber Bungur Pamekasan develop classroom-based curriculum of theÂ Arabic subjects that later termed as classroom curriculum of Arabic subjects.Â The Curriculum development model used is the central de-central, the curriculum development process that combines the two approaches, administrative and grass roots approach. Curriculum development is manifested in the additional hours of lessons and teaching materials, namely on subjects PAI and Arabic which was originally only 11 hours of lessons to 24 hours of lessons. The addition of the lesson period is used to examine the science nahwu, shorrof, hermeneutics (tafsir), and other classical holy books. The factors supporting the implementation of curriculum development are: 1) the Motivation by the Regional Office of the Religion Ministry of East Java, 2) the Principals Commitment, 3) Professional competence of the Arabic subjects classroom teachers, 4) The existence of Islamic boarding school sumber bungurÂ as an institution that strengthens the learning process and 5) the students Input who have an initial understanding of the material that will be presented. While the inhibiting factors are: 1) No allocation of special funds, 2) There is inequality in the ability of teachers in curriculum development, 3) the prevalence of the teachersâ€™s ability in teachingÂ Arabic, and 4) there are someÂ students who feel bored when learning Arabic because of the many hours of lessons being presented.